Preparation method for reducing R angle cracks of ferrite and ferrite material

By adjusting the mold opening orientation and adopting high-precision electric spark processing and coating technology, the problem of ferrite materials prone to cracks at R angles is solved, and the electromagnetic performance and strength of the product are improved.

CN119560291APending Publication Date: 2025-03-04HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702459.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

During the preparation process, ferrite materials are prone to cracks at the R angle, affecting the electromagnetic performance and service life of the product.

Method used

Cracks at the R-angle of the ferrite are reduced by adjusting the orientation of the mold opening and the mold design and production, and using no less than 3 electric spark processing processes and partially coating metal, metal nitride or DLC coatings.

Benefits of technology

It significantly reduces cracks at the R corner of ferrite, improves the electromagnetic performance and overall strength of the product, and is suitable for more stringent use environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560291A_ABST
    Figure CN119560291A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of magnetic material preparation, and particularly relates to a preparation method for reducing ferrite R angle cracks and a ferrite material. The preparation method comprises the following steps: (1) preparing powder; (2) preparing a mold; the step (2) comprises a mold design procedure and a mold manufacturing procedure; and (3) forming. According to the method, R-angle cracks generated in the ferrite preparation process can be remarkably reduced, the problems of magnetic core strength and function attenuation and the like of the ferrite material are prevented, the overall strength of the magnetic core is improved, and the method can be applied to more stringent use environments such as lower and higher use temperature and more bumpy road surfaces.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic material preparation, and in particular relates to a preparation method for reducing ferrite R-angle cracks and a ferrite material. Background Art

[0002] Ferrite materials are widely used in circuits due to their low loss, excellent processability, low price and other advantages. Ferrite cores are brittle materials. The presence of cracks will deteriorate the mechanical strength and even lead to deterioration of electrical performance, higher power, lower carrying power or risks. As the temperature rises, the stress release of the core itself will cause the cracks to deepen further, and even cause the core to break, affecting the use of the device.

[0003] The shape of the ferrite core is designed to be a non-ordinary flat plate, mostly "E"-shaped, "U"-shaped and other complex shapes with turning angles. When preparing the core, the turning angle is generally made into an R angle with a certain curvature. On the one hand, compared with a right angle, the R angle area becomes larger, the molding density is low, and the ferrite on both sides of the R angle shrinks unevenly during the firing process; on the other hand, due to the poor finish of the mold, the ferrite at the R angle is not smoothly demolded during demolding; all of the above situations will cause cracks at the R angle, affecting the electromagnetic properties of the product, and the cracks in the ferrite core cannot be distinguished by the naked eye before sintering, which has a great impact on production efficiency. R angle cracks are a common problem in the ferrite production industry, which will lead to the attenuation of the core strength and function, and there is currently no effective solution. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problem in the prior art that cracks are easily generated at the R corners of ferrites, affecting the electromagnetic properties of the product, thereby providing a preparation method and ferrite material for reducing cracks at the R corners of ferrites.

[0005] To this end, the present invention provides the following technical solutions.

[0006] The present invention provides a preparation method for reducing R corner cracks of ferrite, comprising the following steps:

[0007] (1) preparing powder;

[0008] (2) preparing a mold; the step (2) includes a mold design process and a mold production process;

[0009] (3) Molding;

[0010] The preparation method satisfies at least one of AB:

[0011] A. The mold is provided with an opening, and the direction of the opening is perpendicular to the molding direction;

[0012] B. The mold design process meets the following requirements: the R angle of the mold is not less than R5; and / or, during the molding process, the mold includes at least a floating mold; and / or,

[0013] The mold manufacturing process meets the following requirements: the mold R angle is prepared by using no less than 3 electrospark machining processes; and / or the mold is at least partially coated with a coating, and the material of the coating includes at least one of metal, metal nitride and DLC.

[0014] The present invention adjusts the direction of the mold opening to be perpendicular to the molding direction to reduce cracks at the R corner of the ferrite, thereby ensuring the electromagnetic performance of the product. It should be explained that when the mold opening of the present invention is perpendicular to the molding direction, there are no technical requirements for the R corner of the mold, whether the mold is provided with a floating mold, whether the mold is coated with a coating, etc. The ferrite prepared by conventional methods in the art can achieve the technical effect of not being easy to crack at the R corner.

[0015] When the opening direction is inconsistent with the molding direction, the present invention adjusts the mold design process to ensure that the mold R angle is not less than R5, the mold is provided with a floating mold, at least 3 electrospark machining processes are used in the mold manufacturing process, the mold is partially coated with a coating, and the material of the coating is limited. At least one of the above operations can also reduce the susceptibility to cracks at the ferrite R corner, thereby ensuring the electromagnetic performance of the product.

[0016] Furthermore, on the basis of designing the direction of the mold opening to be perpendicular to the molding direction, further adjusting the mold R angle in the mold design process, providing a floating mold, using at least 3 electric spark machining processes in the mold manufacturing process, and partially coating at least one operation, etc., will help to further ensure the performance of the ferrite and reduce cracks.

[0017] The mold includes an upper mold, a lower mold and a concave mold; the molding positions of the upper mold and the lower mold are coated with the coating, and the upper mold and the lower mold of the mold are coated with the coating to prevent the product from sticking to the mold and causing the product to be defective. Optionally, according to actual needs, the mold also includes a floating mold. The floating mold and the concave mold may be coated with the coating or not.

[0018] Furthermore, the water content of the powder is 0.8-1.2 wt%; and / or,

[0019] The mass proportion of particles with a mesh size of 140 to 200 in the powder is higher than 80%; and / or,

[0020] The powder is stored under sealed conditions for at least 6 hours.

[0021] Furthermore, in step (2), when the material of the coating includes metal or metal nitride, the coating material is selected from at least one of zinc, nickel, chromium, titanium nitride and chromium nitride.

[0022] Furthermore, the coating is selected from at least one of A to F:

[0023] A. The coating is a zinc layer with a thickness of 40 to 80 μm;

[0024] B. The coating is a nickel layer with a thickness of 10 to 80 μm;

[0025] Preferably, the surface hardness of the nickel layer is 450-1000 Hv; and / or the friction coefficient of the nickel layer is 0.2-0.38;

[0026] C. The coating is a chromium layer with a thickness of 5 to 50 μm;

[0027] Preferably, the surface hardness of the chromium layer is 750-1200 Hv; and / or the friction coefficient of the chromium layer is 0.3-0.6;

[0028] D. The coating is a titanium nitride layer with a thickness of 1 to 4 μm;

[0029] Preferably, the surface hardness of the titanium nitride layer is 1000-2300 Hv; and / or the friction coefficient of the titanium nitride layer is 0.33-048;

[0030] E. The coating is a chromium nitride layer with a thickness of 3 to 5 μm;

[0031] Preferably, the surface hardness of the chromium nitride layer is 1500-2200 Hv; and / or the friction coefficient of the chromium nitride layer is 0.1-0.3;

[0032] F. The coating is a DLC layer with a thickness of 0.5 to 2 μm;

[0033] Preferably, the surface hardness of the DLC layer is 1000-4000 Hv; and / or the friction coefficient of the DLC layer is 0.02-0.07.

[0034] Furthermore, the molding includes charging, pressing and demoulding steps.

[0035] Furthermore, after the step (3), the degree of destruction of particles in the area formed by the reverse extension lines of the two right-angled sides of the R angle of the ferrite product obtained by the preparation method is not less than 95%.

[0036] Furthermore, the pressing process adopts a servo press pressing method.

[0037] Furthermore, the parameters of the demoulding process are: a starting angle of 200-220° and an ending angle of 230-255°.

[0038] The present invention provides a ferrite material obtained by the above preparation method.

[0039] The technical solution of the present invention has the following advantages:

[0040] 1. The preparation method for reducing R-angle cracks in ferrite provided by the present invention comprises the following steps: (1) preparing powder; (2) preparing a mold; the step (2) comprises a mold design process and a mold manufacturing process; (3) molding; the preparation method satisfies at least one of AB: A, the mold is provided with an opening, the direction of the opening is perpendicular to the molding direction; B, the mold design process satisfies: the R angle of the mold is not less than R5; and / or, when performing the molding, the mold at least includes a floating mold; and / or, the mold manufacturing process satisfies: the R angle of the mold is prepared by using no less than 3 times of electric spark machining process; and / or, the mold is at least partially coated with a coating, the material of the coating includes at least one of metal, metal nitride and DLC. The method can significantly reduce the R-angle cracks generated in the preparation process of ferrite, prevent the problems of core strength and function attenuation of ferrite materials, improve the overall strength of the core, and can be applied to more stringent use environments, such as lower and higher use temperatures, more bumpy roads, etc. The present invention adjusts the mold opening direction perpendicular to the molding direction, which can avoid low density at the R corner position in the ferrite product, improve uniform density distribution, and reduce cracks; making the mold R angle not less than R5 can adjust the density at the starting point and end point of the R corner of the ferrite product, and reduce the density difference between the powder at the R corner position and the powder at the junction position; using a floating mold can increase the filler at the R corner position of the product, improve the molding density at the R corner position of the ferrite product, and reduce cracks at the R corner; using an electric spark machining process of not less than 3 times to prepare the mold R corner, can improve the smoothness of the mold surface, control the mold to be at least partially coated with a coating, the coating material is at least one of a metal material, a metal nitride and DLC, can improve the mold smoothness, is suitable for powders with higher water content, and is helpful for subsequent demolding processes.

[0041] 2. The preparation method for reducing the R-angle cracks of ferrite provided by the present invention can fully soften the particles in the powder and make them easy to break and deform by controlling the water content of the powder and the sealing time. The particles at the R-angle position can be broken by controlling the pressing process, and the magnetic core is not easily damaged during the demoulding process. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 It is a schematic diagram of the structure and dimensions of the ferrite product U Core in Example 1 of the present invention;

[0044] Figure 2 is a schematic diagram of the mold structure used in Example 1 of the present invention;

[0045] Figure 3 It is a schematic diagram of the structure and dimensions of the ferrite product EC Core in Example 2 of the present invention;

[0046] Figure 4 It is a schematic diagram of the structure of the ferrite product EC Core in Example 2 of the present invention;

[0047] Figure 5 is a schematic diagram of the mold structure used in Example 2 of the present invention;

[0048] Figure 6 It is a schematic diagram of the structure and dimensions of the product in Example 3 of the present invention;

[0049] Figure 7 It is a structural schematic diagram of the product in Example 3 of the present invention;

[0050] Figure 8 is a schematic diagram of the mold structure used in Example 3 of the present invention;

[0051] Reference numerals:

[0052] 1-upper die; 2-ferrite crude product; 3-lower die; 4-die; 5-floating die. DETAILED DESCRIPTION

[0053] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0054] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0055] Example 1

[0056] This embodiment provides a preparation method for reducing R corner cracks of ferrite, comprising the following steps:

[0057] (1) Preparation of powder

[0058] The inlet temperature of the granulation tower was adjusted to 225°C, the outlet temperature was adjusted to 250°C, and the spray gun aperture was adjusted to 1.2mm to obtain the PC40 powder to be formed. By testing the moisture content and particle distribution, it was found that the moisture content of the powder was 0.93%, the proportion of 140-200 mesh particles was 88.24wt%, and it was sealed and stored for 8h.

[0059] (2) Mold Preparation

[0060] Mold design process: The ferrite product is the U Core used in conjunction with UI. The structure and size of the U Core can be found in Figure 1 , Figure 1 Figure a is the front view of the ferrite product. Figure 1 Figure b is a top view of the ferrite product. The mold structure and size correspond to the product. The mold structure is shown in Figure 2 The mold is provided with an opening, the opening direction is perpendicular to the molding direction, and the opening direction is referenced Figure 1 The arrow b in the middle points to the direction of molding. Figure 1 The arrow in a points to and Figure 2 The middle arrow points to a direction where the mold has no floating mold, the R angle of the mold is R0.3, and the mold includes an upper mold 1, a lower mold 3 and a concave mold 4.

[0061] Mold manufacturing process: The mold R angle is prepared by three electrospark machining processes, which are R0.2, R0.25, and R0.3 respectively; the upper and lower mold surfaces of the mold are chrome-plated, and the friction coefficient of the chrome coating is 0.6 and the surface hardness is 1000Hv.

[0062] (3) Molding includes charging, pressing and demolding, and the crude ferrite product is obtained after demolding. After molding, the degree of destruction of the particles of the crude ferrite product in the area formed by the reverse extension lines of the two right angles of the R angle of the crude ferrite product is not less than 95%. Among them, the parameters of the demolding process are: the starting angle is 200-220°, and the ending angle is 230-255°.

[0063] Sintering: Put the crude ferrite into a push plate kiln for sintering to obtain a ferrite product; wherein, the sintering temperature is 1330±30℃, and the time is about 40h.

[0064] R angle detection: Use electronic magnifying glass CCD to magnify 30 times to observe whether there are cracks at the R angle of ferrite products; test results: No R angle cracks were found in ferrite products.

[0065] Example 2

[0066] This embodiment provides a preparation method for reducing R corner cracks of ferrite, comprising the following steps:

[0067] (1) Preparation of powder

[0068] The inlet temperature of the granulation tower was adjusted to 225°C, the outlet temperature was adjusted to 250°C, and the spray gun aperture was adjusted to 1.2mm to obtain the PC40 powder to be formed. By testing the moisture content and particle distribution, it was found that the moisture content of the powder was 1.05%, the proportion of 140-200 mesh particles was 83.38wt%, and it was sealed and stored for 10 hours.

[0069] (2) Mold Preparation

[0070] Mold design process: The ferrite product is EC Core. The structure and size of the EC Core product are shown in Figure 3 , Figure 3 A is the front view of the product. Figure 3 Figure b is a top view of the product. Figure 4 This is a schematic diagram of the EC Core product structure. The mold has the same structure and size as the product. The mold structure is shown in Figure 5 The mold is provided with an opening, the direction of the opening is parallel to the molding direction, refer to Figure 3 The arrow a in the middle points to the R angle of the mold, which is R0.1. The mold includes an upper mold 1, a lower mold 3, a concave mold 4 and a floating mold 5; wherein, Figure 5 2 in the middle is the crude ferrite, i.e. the powder filling position.

[0071] Mould manufacturing process: The R angles are prepared by three electrospark machining processes, which are R0.06, R0.09, and R0.1 respectively; then the upper and lower mould surfaces in the mould are plated with chrome coating, the friction coefficient of the chrome coating is 0.6, and the surface hardness is 800Hv.

[0072] (3) Forming includes charging, pressing and demoulding, using a concave mold; after demoulding, a crude ferrite product is obtained. After forming, the degree of destruction of the particles of the crude ferrite product in the area formed by the reverse extension lines of the two right angles of the R angle of the crude ferrite product is not less than 95%. Among them, the parameters of the demoulding process are: the starting angle is 200-220°, and the ending angle is 230-255°.

[0073] Sintering: Put the crude ferrite into a push plate kiln for sintering to obtain a ferrite product; wherein, the sintering temperature is 1330±30℃, and the time is about 40h.

[0074] R corner detection: Use CCD to magnify 30 times to observe whether there are cracks at the R corner of the ferrite product; test results: No R corner cracks were found.

[0075] Example 3

[0076] This embodiment provides a preparation method for reducing R corner cracks of ferrite, comprising the following steps:

[0077] (1) Preparation of powder

[0078] The inlet temperature of the granulation tower was adjusted to 225°C, the outlet temperature was adjusted to 250°C, and the spray gun aperture was adjusted to 1.2mm to obtain the PC40 powder to be formed. By testing the moisture content and particle distribution, it was found that the moisture content of the powder was 0.88%, the proportion of 140-200 mesh particles was 89.76wt%, and it was sealed and stored for 7h.

[0079] (2) Mold Preparation

[0080] Mould design process: product structure and size see Figure 6-7 , Figure 6 This is the front view of the product structure and dimensions. Figure 7 This is a schematic diagram of the product structure. Figure 7 The red arrow in the figure represents the R angle of the product. The structure and size of the mold correspond to the product. Figure 8 The mold is provided with an opening, the direction of the opening is parallel to the molding direction, and the molding direction is referenced Figure 6 The arrow points to the R angle of the mold, which is R10. The mold includes an upper mold 1, a lower mold 3, a concave mold 4 and a floating mold 5. 2 is a ferrite rough product.

[0081] Mold manufacturing process: The R angles are prepared by three electrospark machining processes, namely R7, R9, and R10; then the upper and lower molds in the mold are chrome-plated on the surface. The friction coefficient of the chrome coating is 0.4 and the surface hardness is 1100.

[0082] (3) Forming includes charging, pressing and demoulding, using a concave mold; after demoulding, a crude ferrite product is obtained. After forming, the degree of destruction of the particles of the crude ferrite product in the area formed by the reverse extension lines of the two right angles of the R angle of the crude ferrite product is not less than 95%. Among them, the parameters of the demoulding process are: the starting angle is 200-220°, and the ending angle is 230-255°.

[0083] Sintering: Put the crude ferrite into a push plate kiln for sintering to obtain a ferrite product; wherein, the sintering temperature is 1330±30℃ and the time is about 40h.

[0084] After testing, no R-corner cracks were found in the ferrite products.

[0085] Comparative Example 1

[0086] This comparative example provides a preparation method for reducing cracks in the R corner of ferrite, which is different from Example 1 in that the mold making process uses a single electric spark machining process to prepare the R corner, and mechanical pressing is used instead of the servo press pressing process. It is found through testing that cracks are generated in the R corner.

[0087] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A preparation method for reducing R corner cracks in ferrite, characterized in that: The following steps are involved: (1) preparing powder; (2) preparing a mold; the step (2) includes a mold design process and a mold production process; (3) Molding; The preparation method satisfies at least one of AB: A. The mold is provided with an opening, and the direction of the opening is perpendicular to the molding direction; B. The mold design process meets the following requirements: the R angle of the mold is not less than R5; and / or, during the molding process, the mold includes at least a floating mold; and / or, The mold manufacturing process meets the following requirements: the mold R angle is prepared by using no less than 3 electrospark machining processes; and / or the mold is at least partially coated with a coating, and the material of the coating includes at least one of metal, metal nitride and DLC.

2. The preparation method according to claim 1, characterized in that: The water content of the powder is 0.8-1.2 wt %; and / or, The mass proportion of particles with a mesh size of 140 to 200 in the powder is higher than 80%; and / or, The powder is stored under sealed conditions for at least 6 hours.

3. The preparation method according to claim 1 or 2, characterized in that: In the step (2), when the material of the coating includes metal or metal nitride, the coating material is selected from at least one of zinc, nickel, chromium, titanium nitride and chromium nitride.

4. The preparation method according to claim 3, characterized in that: The coating is selected from at least one of A to F: A. The coating is a zinc layer with a thickness of 40 to 80 μm; B. The coating is a nickel layer with a thickness of 10 to 80 μm; Preferably, the surface hardness of the nickel layer is 450-1000 Hv; and / or the friction coefficient of the nickel layer is 0.2-0.38; C. The coating is a chromium layer with a thickness of 5 to 50 μm; Preferably, the surface hardness of the chromium layer is 750-1200 Hv; and / or the friction coefficient of the chromium layer is 0.3-0.6; D. The coating is a titanium nitride layer with a thickness of 1 to 4 μm; Preferably, the surface hardness of the titanium nitride layer is 1000-2300 Hv; and / or the friction coefficient of the titanium nitride layer is 0.33-048; E. The coating is a chromium nitride layer with a thickness of 3 to 5 μm; Preferably, the surface hardness of the chromium nitride layer is 1500-2200 Hv; and / or the friction coefficient of the chromium nitride layer is 0.1-0.3; F. The coating is a DLC layer with a thickness of 0.5 to 2 μm; Preferably, the surface hardness of the DLC layer is 1000-4000 Hv; and / or the friction coefficient of the DLC layer is 0.02-0.

07.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The molding process includes charging, pressing and demoulding processes.

6. The preparation method according to claim 5, characterized in that: After the step (3), the degree of destruction of particles in the area formed by the reverse extension lines of the two right-angled sides of the R angle of the ferrite product obtained by the preparation method is not less than 95%.

7. The preparation method according to claim 5, characterized in that: The pressing process adopts a servo press pressing method.

8. The preparation method according to claim 7, characterized in that: The parameters of the demoulding process are as follows: the starting angle is 200-220°, and the ending angle is 230-255°.

9. The ferrite material obtained by the preparation method according to any one of claims 1 to 8.